The Effect of Educational Game Tools Rotating Series Story Cards on The Speaking Ability of Children 5-6 Years Old at TKIT Shalih Child Character Padang - Tanjung, Dian Puspita; Puridawaty , Brigita (Kirana Publisher (KNPub), 2024)
The purpose of this study was to analyze the extent of the influence of the use of Rotating Series Story Cards on the speaking ability of children aged 5-6 years at TKIT Karakter Anak Shalih Padang. The type of research used is quantitative experimental research (Quasi Experimental Design), with a Nonequivalent Posttest-Only Control Group Deign approach), The research population is 5-6 year old children in Group B1 as the experimental class and B2 as the control class with a total of 30 students. Data collection was carried out by observation and checklists. Data analysis was carried out using SPSS 24.0, using tests and hypotheses. Based on the results of the study, it shows that there is a significant effect of using educational game tools for rotating series story cards on the speaking ability of children aged 5-6 years at TKIT Karakter Anak Shalih Padang, it can be seen from the statistical test results Based on the results of the Independent Sample T-test test, it can be seen that the significance value is 0.171 indicating that 0.171 ≥ 0.01 then ????0 is accepted. So it can be concluded that there is an effect of using educational game tools Rotating Series Story Cards on the speaking ability of children aged 5-6 years in TKIT Karakter Anak Shalih Padang.